광주지역에 거주하는 결혼이주 여성의 식생활 조사 - 양은주(Yang, Eun Ju) (Journal of nutrition and health, 2016)
Purpose: This cross-sectional study aimed to document the dietary behaviors, dietary changes, and health status of female marriage immigrants residing in Gwangju, Korea. Methods: The survey included 92 female immigrants attending Korean language class at a multi-cultural family support center. General characteristics, health status, anthropometric data, dietary behaviors, and dietary changes were collected. Results: Mean age of subjects was 31.3 years, and home countries of subjects were Vietnam (50.0%), China (26.0%), Philippines (12.0%), and others (12.0%). Frequently reported chronic diseases were digestive diseases (13.2%), anemia (12.1%), and neuropsychiatry disorder (8.9%). Seventeen percent of the subjects was obese ($BMI{≥}25kg/m^2$). Dietary score by Mini Dietary Assessment was 3.45 out of 5 points. Dietary scores for dairy foods, meat/fish/egg/bean intake, meal regularity, and food variety were low, and those for fried foods and high fat meat intake were also low. Thirty-three percent of subjects answered that they have changed their diet and increased their consumption of fruits and vegetables after immigration. Length of residence in Korea was positively associated with BMI and waist circumference. Length of residence tends to be positively associated with dietary changes and obesity as well as inversely associated with disease prevalence. Conclusion: The study shows that length of residence is inversely related to disease prevalence. However, this association is thought to be due to the relatively short period of residence in Korea and thus the transitional phase to adapting to dietary practices. As the length of residence increases, disease patterns related to obesity are subject to change. Healthy dietary behaviors and adaptation to dietary practices in Korea in female marriage immigrants will not only benefit individuals but also their families and social structure. Therefore, varied, long-term, and target-specific studies on female marriage immigrants are highly needed. 본 연구는 광주광역시에 거주하는 결혼이주여성 92명을 대상으로 하여 사회경제적 특징과 건강, 식생활 실태를 조사하여 결혼이주 여성의 식생활과 이에 영향을 미치는 요인을 분석하기 위해 수행되었다. 본 조사에 응한 결혼이주여성의 평균 연령은 31.3세, 한국에서의 평균 거주기간은 5.5년이었으며, 출신국은 베트남 56%, 중국 26%, 필리핀 12%, 기타 국가 12% 등이었다. 가장 많이 앓고 있는 질병은 소화기계 질환, 빈혈, 신경계 질환 순이었고, 만성 성인병 유병률은 낮은 편이었다. 조사대상자의 체위를 살펴보면, 현재 평균 체중은 54 kg으로서, 한국으로 이주할 때 체중과 비교하면 평균 3.8 kg 증가하였으며, BMI $25kg/m^2$를 기준으로 비만한 조사대상자는 17%였다. 식품을 구입할 때 가장 중요하게 생각하는 것은 영양적 가치, 건강, 식품에 대한 기호도 순으로 건강에 관심이 높았으며, 식품에 대한 정보는 인터넷 37.0%, 가족 28.3%, TV 또는 라디오 27.2% 순으로 스마트폰 사용이 일반화되어 인터넷을 통한 정보습득이 가장 많았다. Mini dietary assessment로 판정한 식습관점수는 5점 만점 기준에 3.45이었으며, 유제품 섭취, 단백질 섭취, 규칙적 식사, 골고루 섭취하기 등에서 점수가 낮은 경향을 나타냈으나, 지방이 많은 음식이나 동물성 지방, 튀긴 음식, 당이나 탄산음료도 적게 섭취하였다. 조사대상자의 식습관 변화정도를 살펴보면, 한국으로 이주 후 식습관이 많이 변했다고 응답한 조사대상자는 33.7%였으며, 식습관 변화 내용으로는 식품섭취 증가와 관련되었으며, 특히 과일과 채소의 섭취가 증가하였다고 응답하였다. 조사대상자의 거주 기간이 BMI, 허리둘레와 유의적으로 양의 상관관계 있었으며, 거주 기간별로 비만, 질병 유병, 식습관 변화 정도를 살펴본 결과, 유의적인 차이는 없었으나, 거주기간이 5년 이상인 그룹이 5년 미만인 그룹에 비해 식습관이 많이 변하고 비만율이 증가하였으나 질병은 감소하는 경향을 나타냈다. 본 연구 결과에서는 거주기간과 질병 유병률이 역의 관계가 있는 것으로 보고되었으나, 이는 본 조사대상자의 한국 평균 거주기간이 비교적 짧아 한국 문화에 대한 적응단계가 이행단계와 관계되는 것으로 생각된다. 결혼이주 여성의 식생활 적응 및 바람직한 식습관 형성은 결혼이주 여성 뿐 만 아니라 이들이 속하고 책임지고 있는 다문화 가정의 건강에도 중요한 영향을 미칠 것으로 사료되어 결혼이주 여성에 대한 장기적이고 다양한 연구와 교육이 필요할 것이다.